EFEKTIVITAS PEMBELAJARAN DEFERENSIASI DALAM MENGOPTIMALKAN HASIL BELAJAR SISWA - Hasanah, Siti Nur; Rahmawati, Dini; Handayani, Arri (Universitas Tanjungpura, 2026)
In the world of education, the main challenge faced by teachers is the diversity of student characteristics in one class. Differentiated learning strategies offer significant potential to increase learning effectiveness for students at various levels. The aim of this research is to evaluate the effectiveness of differentiated learning so that students can achieve optimal learning outcomes. Identifying the advantages and effective implementation methods for implementing differentiated learning at various levels of education is the main focus of this research. This article was written using a qualitative approach to literature review, which includes critical analysis of relevant articles. Ten articles published within the last five years